Adsorption and photo degradation for organic pollutants in wastewater using copper oxide based on waste cotton impregnated with sodium hydroxide (CuO/NaOH/CW) composites - Hassan, Ali A.; Shakir, Ibtehal K.; Al-Lami, Munaf (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
This work prepared new composite (CuO/NaOH/CW) and compared with another composite (HNO3/NaOH/CW) from cotton waste, sodium hydroxide, copper sulphate and nitric acid for the treatment of refinery wastewater. Dry weight analysis confirmed the attachment of 29 and 32 % NPs in the composites of copper oxide and nitric acid, and their observed slow-release behavior contributed to enhanced stability. The accessory of copper oxide to the cotton waste surface fibrils and their deep infiltration into the matrix were obviously established by characterization analysis. The composite material was evaluated for its adsorption and photodegradation capabilities for organic removal from refinery wastewater (RWW). Remarkably, the synthesized composites exhibited impressive waste cotton activities against organic pollutants, achieving reduction rates of 89.2%, 78.4%, and 55.4% for CuO/NaOH/CW, HNO3/NaOH/CW, and NaOH/CW, respectively. The cotton waste based CuO composites demonstrated non-toxicity and catalytic behavior under UV light exposure, offering insights for potential applications in organic pollutant removal and environmental remediation.